Microscale Lithium Metal Stored inside Cellular Graphene Scaffold toward Advanced Metallic Lithium Anodes. Issue 12 (19th January 2018) - Deng, Wei; Zhou, Xufeng; Fang, Qile; Liu, Zhaoping
Abstract: The volume expansion and dendrite growth of metallic Li anode during charge/discharge processes hinder its practical application in energy storage. Seeking an appropriate host for distributing bulk Li in a 3D manner is an effective way to solve these problems. Here, a novel porous graphene scaffold with cellular chambers for incorporating Li metal is presented. Using such a unique host, ultrathin Li layers of 3 µm in thickness are anchored on graphene to form porous microstructures, which provides much more reaction sites for Li ions compared with that of bulk Li, significantly promoting the reversibility of Li stripping and plating. Also the high current density can be effectively dissipated by the graphene scaffold to remarkably improve the rate capability of Li anode. The symmetrical Li cell using such a Li anode can run stably for 200 cycles at 5 mA cm −2 and even 70 cycles at 10 mA cm −2 in an unmodified carbonate‐based electrolyte, which has rarely been achieved in such aggressive working conditions. Lithium‐ion capacitor cells using this anode also show outstanding rate capability and cycling stability, which can work at an ultrahigh current density of 30 A g −1 and keep steady for over 4000 cycles at 3.75 A g −1 . Abstract : An advanced metallic lithium anode is fabricated by pre‐storing ultrathin Li metal layered in a cellular graphene scaffold. Microscale Li metal anchored on graphene sheets facilitates the overall electron reaction and dendrite‐suppressed deposition of Li metal. This graphene scaffold enhanced Li metal anode shows exceptionally high rate capability and cycling stability in both Li symmetrical cells and Li‐ion capacitors.